A Rare Case of Familial Adenomatous Polyposis in South Eastern Nigeria: A Case Report and Review of the Literature - Kenneth A. Agu; Jude K. Ede; EvanTherese Nwosu; Ikechukwu S. Eze; Emeka Eze; Chukwuemelie B. Okechukwu; Ifeoma Madichie (International Journal of Medicine and Health Development)
Familial adenomatous polyposis syndrome (FAP) is a rare multisystemic disorder that affects individuals who have mutation in the adenomatous polyposis coli (APC) gene. If left untreated, the polyps progress over a period of 15–20 years to adenocarcinoma in virtually 100% of cases. The syndrome is uncommon worldwide and very rare in Nigeria. We report the case of a 45-year-old male who presented with recurrent lower gastrointestinal bleeding and change in bowel habits. Hundreds of colonic polyps were identified at colonoscopy, with two large colonic tumors that were observed to be partially obstructing the bowel. There were some extracolonic findings during further investigations. Histology of the obstructing tumors confirmed colonic adenocarcinoma. The patient had detailed clinical evaluation, further diagnostic investigations, and optimization. He subsequently had exploratory laparotomy and total colectomy with ileo-rectal anastomosis and was scheduled for chemotherapy and surveillance for the rectal sleeve using proctoscopy. He will also be monitored for gastric and duodenal polyps.